COMPLIANCE AND NON-COMPLIANCE IN THE PREPARATION AND ADMINISTRATION OF ANTIBACTERIAL DRUGS - Francisco Gilberto Fernandes Pereira; Gabriel Ângelo de Aquino; Geórgia Alcântara Alencar Melo; Carolina de Oliveira Praxedes; Joselany Áfio Caetano (Universidade Federal do Paraná, 2016)
The present study aimed to assess compliance and non-compliance in the preparation and administration of antibacterial drugs. Observational and cross-sectional study conducted from August to December 2014 in medical wards of a teaching hospital in Fortaleza-Ceará. The sample was composed by 265 doses of antibacterial drugs whose preparation and administration stages were observed during the three work shifts, with two checklists. Data were analyzed using descriptive statistics, and all ethical procedures were fulfilled. The most frequent non-compliance observed in both stages was compliance withthe requirements of the several techniques performed by nursing professionals (semiotechnique), 265 (100%). The hospital organization was associated with error in the choice of the (p=0.027), and the use of prescription and confirmation of patient's identity were not related to the errors (p=0.942). Thus, it is concluded that behavioral changes in the work process should be implemented to reduce non-compliance and, consequently, medication errors.